Imidazolium group prompted alkaline anion-exchange membrane with high performance for efficient electrochemical CO2 conversion - Wang, Min; Zou, Qianqian; Dong, Xueqi; Xu, Nengneng; Shao, Rong; Ding, Jianfei; Zhang, Yidong; Qiao, Jinli (Green energy & environment, 2023)
Development of high-performance hydroxide-conductive membranes is a focus research subject owing to promising applications in electrochemical reduction of CO2 (eCO2RR). However, few satisfactory membranes have been developed to maximize the performance of CO2 electrolyzers, despite its role as the core in regulating ion transport and preventing product crossover or fuel loss. Herein, we report the synthesis of alkaline anion-exchange membranes fabricated by poly (vinyl-alcohol) (PVA) and poly [(3-methyl-1-vinylimidazoliummethylsulfate)-co-(1-vinylpyrrolidone)] (PQ44) for use in CO2 electrolysis. Owing to the unique imidazolium ring structure coupled with a three-dimensional semi-interpenetrating porous internal architecture, the PVA/PQ44-OH- membranes provide a high hydroxide conductivity (21.47 mS cm−1), preferable mechanical property and thermal stability. In particular, the eCO2RR used PVA/PQ44-OH- as electrolyte membrane realized a charming Faradaic efficiency (88%) and partial current density (29 mA cm−2) at −0.96 VRHE and, delivered the excellent durability over 20 h electrolysis in 0.5 mol L−1 KHCO3 electrolyte. Notably, it can even enable an ultrahigh current density beyond 100 mA cm−2 at −1.11 VRHE when the electrolyte was KOH instead, and produced the FEHCOO− of 85% at a low potential of −0.81 VRHE, superior to both commercial alkaline A201 and acidic Nafion117 membrane. The AEMs is prepared by a combined method including thermal and chemical cross-linking, and blending technique using polymer PVA and PQ44. Acetal reaction during chemical cross-linking indicates that PQ44 has been successfully “trapped” into the polymer skeleton of PVA, forming a 3D semi-interpenetrating porous network. Owing to the imidazolium ring coupled with the unique architecture, the as-prepared membranes exhibited superior performance in practical application on electrochemical reduction of CO2. Schematic illustration of the preparation procedure for the PVA/PQ44-OH- membrane. [Display omitted] •The membrane has a three-dimensional semi-interpenetrating porous internal architecture.•The membrane was biodegradable and prepared by a mild solution-casting method.•The imidazolium groups enhance the chemical stability and improve the durability of the membranes.•The self-made membrane shows excellent current density and FEHCOO− in eCO2RR.